NEW SPECIES OF THE FAMILY HELIODISCIDAE HAECKEL (RADIOLARIA) - Vishnevskaya V.S. (My University, 2006)
The family Heliodiscidae Haeckel, 1881, which includes five genera, is reviewed. New methods of investigation are applied to the inner structure of Cretaceous spherical radiolarian skeletons, which reveal numerous taxa with an eccentric microsphere. Three new species, Astrophacus marinae sp. nov., Excentrosphaerella kovalenkovi sp. nov., and Excentrosphaerella kurilovi sp. nov., are described. The eccentric position of the microsphere suggests that these forms are nontypical Mesozoic radiolarians or new representatives of the family Heliodiscidae Haeckel, 1881, which was previously recorded in the Cenozoic. © Pleiades Publishing, Inc. 2006.
Keywords: CRETACEOUS; HELIODISCIDAE; NEW SPECIES; RADIOLARIA; Mesozoic::Cretaceous; Мезозой::Меловая